Stealth Acquisitions and Product Market Competition - KEPLER, JOHN D.; NAIKER, VIC; STEWART, CHRISTOPHER R. (Journal of Finance, 2023)
ABSTRACT We examine whether and how firms structure their merger and acquisition deals to avoid antitrust scrutiny. There are approximately 40% more mergers and acquisitions (M&As) than expected just below deal value thresholds that trigger antitrust review. These “stealth acquisitions” tend to involve financial and governance contract terms that afford greater scope for negotiating and assigning lower deal values. We also show that the equity values, gross margins, and product prices of acquiring firms and their competitors increase following such acquisitions. Our results suggest that acquirers manipulate M&As to avoid antitrust scrutiny, thereby benefiting their own shareholders but potentially harming other corporate stakeholders.